2017
DOI: 10.5539/elt.v10n6p12
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Female Teachers’ Perceptions of the Use of L1 in EFL Classrooms

Abstract: In the literature of second language teaching and learning, the use of students' first language (L1) has been an issue of debate for many years. Despite the changing state of teaching and learning aspects over the years, the belief that L1 should not be used in English as a Foreign Language (EFL) classrooms has stood the test of time. Nevertheless, many studies have recently started to put this belief under question and to give the effectiveness of L1 use, the benefit of doubt. This paper investigates EFL teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The first clarification is based on the questionnaire data divided into three contexts: preteaching activity, whilst teaching activity, and postteaching activity. It is because the use of L1 in English class depends on the material, activity, task, and needs of the students and the goal of the class (Karatas, 2016;Al-Amir, 2017;Shabir, 2017). Moreover, the discussion continues with the teachers' perspectives I n P r e s s about their reason for using L1 in their English class.…”
Section: Resultsmentioning
confidence: 99%
“…The first clarification is based on the questionnaire data divided into three contexts: preteaching activity, whilst teaching activity, and postteaching activity. It is because the use of L1 in English class depends on the material, activity, task, and needs of the students and the goal of the class (Karatas, 2016;Al-Amir, 2017;Shabir, 2017). Moreover, the discussion continues with the teachers' perspectives I n P r e s s about their reason for using L1 in their English class.…”
Section: Resultsmentioning
confidence: 99%
“…A considerable amount of literature has focused on teachers' and learners' perceptions of CS in EFL classrooms. For instance, previous studies have confirmed that teachers and learners showed positive attitudes and acceptance of CS in EFL classrooms (e.g., AbdelMagid & Mugaddam, 2013;Al Adnani & Elyas, 2016;Al-Amir, 2017;Al-Balawi, 2016;Alkhudair, 2019;Al-Nofaie, 2010;Yao, 2011). Al-Nofaie (2010) argued that CS is an unavoidable phenomenon.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Challenges and Considerations: Despite the numerous benefits of digital media technology in Arabic and English classes in Jordan, there are also challenges and considerations that need to be addressed. These include issues of access to technology and reliable internet connectivity, ensuring the quality and authenticity of online resources, addressing concerns about privacy and security, and providing adequate training and support for teachers and students to effectively use digital media technology for language learning (Martnez Lirola, 2020;Al-Amir, 2017;Muhsen Al Harbi, 2017;Goundar, 2019).…”
Section: Cultural Exchange and Authentic Language Usementioning
confidence: 99%